THE EFFECT OF THE ACTIVIST TEACHER EDUCATION PROGRAM ON IMPROVING THE QUALITY OF TEACHER EDUCATION - Kholisoh, Lilis; Lismawati, Lilis; Sutarsana, Sutarsana; Kharismawan, Depi; Herliana, Eli (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The study aims to show that the idea of self-directed learning is a teacher mobilization program with a view to improving educational standards. The research method for this article is a literature review of twenty journal articles from various sources. Keywords such as “quality of education”, self-learning”, and “teacher driving” were used the search process. As a first step, the aouthors compiled a list of specific questions for each article. The following are the research questions: 1) What is the current picture of the quality of education in Indonesia? 2) What factors influence educational standards? 3) In what ways does the idea of self-study apply to you? The study pindings from the literature review show that educational issues cannot be separated from the teacher’s leadership role. The teacher’s leadership role in promoting the idea of independent learning, Where The Teacher Driving Education Program has six effects that improve the quality of teacher education at SDN 1 Panawangan Ciamis Regency: 1) Increasing student academic achievement, 2) Creating a creative process of Teaching and Learning Activities (KBM), 3) Encouraging educators and education staff to improve competency, 4) Developing student’s abilities holistically, 5) Providing direction and guidance to educators and educational staff to carry out student-centered teaching and learning activities, and 6) As a model and agent of transformation in the world of education